«Керченско–Эльтигенская операция» на уроке истории в школе: 70-летию памяти посвящается - Дмитрук, Д.В. (Культура народов Причерноморья, 2014)
Статья заслуженного учителя АР Крым, учителя-методиста УВК «Школы-лицея» № 3 г.
Симферополь Дмитрия Васильевича Дмитрука представляет собой учебно-методическую разработку
урока, посвященную событиям Второй мировой войны, изложенную в рекомендательной форме.
События Керченско-Эльтигенского десанта, их семидесятилетний юбилей отражены в теме урока
«Керченско-Эльтигенская десантная операция». Разработка и проведение занятия, практический и
эмпирический опыт легли в основу данной методической статьи. Автор изыскания четко и системно
излагает ход урока. Статья может быть полезна для учителей с небольшим педагогическим стажем,
студентам-историкам, проходящим практику в общеобразовательных школах, а также всем
интересующимся педагогикой. Стаття заслуженого вчителя АР Крим, вчителя-методиста НВК «Школа-ліцей» № 3 м.
Сімферополя Дмитра Васильовича Дмитрука складає навчально-методичну розробку уроку, що
присвячена подіям Другої світової війни і викладена в рекомендаційній формі. Події Керченсько -
ельтигенського десанту, їх сімдесятирічний ювілей відображені в темі уроку «Керченсько -
ельтигенська десантна операція». Розробка і проведення заняття, практичний і емпіричний досвід лягли
в основу даної методичної статті. Автор дослідження чітко і системно викладає хід уроку. Стаття
може бути корисна для вчителів з невеликим педагогічним стажем, студентам- історикам, які
проходять практику в загальноосвітніх школах, а також всім, хто цікавиться педагогікою. Article honored teacher of Crimea, teacher-methodologist UCMJ "School - Lyceum» № 3 Simferopol
Dmitry Vasilyevich Dmitruk is an educational - methodical development of the lesson devoted to the events of
World War II, as set out in the form of advisory. Events Kerch-Eltigensky landing their seventieth birthday
reflected in the lesson "Kerch-Eltigensky amphibious operation". Develop and conduct classes, practical and
empirical experience, formed the basis of this methodological articles. Author surveys clearly and systematically
presents the course of the lesson. The article can be useful for teachers with little teaching experience, students
of history, passing practice in secondary schools, as well as all those interested in pedagogy.
The Kerch–Eltigen Operation was a World War II amphibious offensive made in November 1943 by the Red
Army as a precursor to the Crimean Offensive (8 April-12 May 1944) with the object of defeating and forcing the
withdrawal of the German forces from the Crimea. Landing at two locations on the Crimea's eastern coast, the
Red Army successfully reinforced the northern beachhead of Yenikale, but was unable to prevent an Axis counterattack that collapsed the southern beachhead at Eltigen. Subsequently, the Red Army used the beachhead at
Yenikale to launch further offensive operations into the Crimea in May 1944.